Immunocytochemistry, assisted by computer image analysis, of hypophyseal peptide hormones of the impala (Aepyceros melampus) - Meltzer, David George Anton (University of Pretoria, 2013)
Dissertation (MMed Vet (FER))--University of Pretoria, 1999.